The Prospects and Challenges in the Practice of Islamic Medicine in Ibadan, Nigeria - Oniye (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
The practice of Islamic medicine is becoming a household activity in the city of Ibadan today. Every nook and cranny of the city has at least an Islamic medical clinic where patients are admitted and treated according to Islamic prescriptions. Its inception has brought about some changes both among Muslims and in the medical practice in the land. This study intends to examine the practice vis-à-vis the inherent prospects and challenges of venturing into the practice. A historical method of research is adopted to achieve the objectives of this paper. This is imperative considering the nature of the topic of this paper which is deeply rooted in history. It is discovered that their profession can be made from the practice and the future is bright for the practitioners. It provides job opportunities, strengthens the Muslim faith and is relatively affordable. On the other hand, the practice is faced with many problems and challenges which the practitioners have not been able to put behind them, such includes misconceptions between Jalabi and Islamic medical practice, financial inadequacies, lack of knowledge and unfavorable government policies among others. The paper therefore concluded that the future of Islamic medicine in Ibadan is brighter but the practitioners need to surmount those challenges to strengthen the practice in the city.